Three Month Follow-Up of Patients With COVID-19 Pneumonia Complicated by Pulmonary Embolism - Calabrese, Cecilia; Annunziata, Anna; Flora, Martina; Mariniello, Domenica Francesca; Allocca, Valentino; Palma, Maria Ilaria; Coppola, Antonietta; Meoli, Ilernando; Pafundi, Pia Clara; Fiorentino, Giuseppe (Frontiers in Molecular Biosciences, 2022)
Background: Previous studies have demonstrated persistent dyspnoea and impairment of respiratory function in the follow-up of patients who have recovered from COVID-19 pneumonia. However, no studies have evaluated the clinical and functional consequences of COVID-19 pneumonia complicated by pulmonary embolism. Objective: The aim of our study was to assess the pulmonary function and exercise capacity in COVID-19 patients 3 months after recovery from pneumonia, either complicated or not by pulmonary embolism. Methods: This was a retrospective, single-centre, observational study involving 68 adult COVID-19 patients with a positive/negative clinical history of pulmonary embolism (PE) as a complication of COVID-19 pneumonia. Three months after recovery all patients underwent spirometry, diffusion capacity of the lungs for carbon monoxide (DLCO), and 6 minute walk test (6MWT). In addition, high-resolution computed tomography (HRCT) of the lung was carried out and CT-pulmonary angiography was conducted only in the PE+ subgroup. Patients with a previous diagnosis of PE or chronic lung diseases were excluded from the study. Results: Of the 68 patients included in the study, 24 had previous PE (PE+) and 44 did not (PE−). In comparison with the PE− subgroup, PE+ patients displayed a FVC% predicted significantly lower (87.71 ± 15.40 vs 98.7 ± 16.7, p = 0.009) and a significantly lower DLCO% predicted (p = 0.023). In addition, a higher percentage of patients were dyspnoeic on exercise, as documented by a mMRC score ≥1 (75% vs 54.3%, p < 0.001) and displayed a SpO2 <90% during 6MWT (37.5% vs 0%, p < 0.001). HRCT features suggestive of COVID-19 pneumonia resolution phase were present in both PE+ and PE− subjects without any significant difference (p = 0.24) and abnormalities at CT pulmonary angiography were detected in 57% of the PE+ subgroup. Conclusion: At the 3 month follow-up, the patients who recovered from COVID-19 pneumonia complicated by PE showed more dyspnoea and higher impairment of pulmonary function tests compared with those without PE.